PENGARUH KOMPOSISI MEDIA TANAM DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN Anthurium hookeri - Indrawati Indrawati; TYAS SUMARAH KURNIA DEWI; W. WIYONO (JURNAL ILMIAH AGRINECA, 2016)
This research is conducted in Yamansari Lebaksiu Subdistrict, Tegal District, from Juni until August 2011 this research aim to know: (1) the effect of composition of media plant and the dose fertilizer NPK to growth of crop of Anthurium hookeri (2) composition of media plant and the dose fertilizer NPK the affected of good to growth of crop of Anthurium hookeri.( 3 ) these treachmentgiving combination that composition of media plantond the dose fertilizer NPK to growthof crop of Anthurium hookeri. Method used in this research is experiment method, method by usingÂ  Randommyzed Complete design ( RCD ). Consist of two factors, composition media plant (M) and the dose fertilizer NPK , ( D) with repeated by three. Treatment combination is : M1D1 ( CP: AS: SK= 1: 1: 1 and 6 g NPK / polibag),M2D1 (CP : AS: SK=2 : 1: 1 and 6 NPK/ polibag), M3D1 (CP : AS: SK= 1 : 2 : 1 and 6 g NPK/polibag), M4D1 (CP : AS: SK = 1: 1 : 2 and 3 g NPK /polibag), M1D2 (CP : AS : SK =Â  1 : 1 : 1 and 5 g NPK/polibag), M2D2 (CP : AS : SK = 2: 1: 1 and 5 g NPK/polibag), M3D2 (CP : AS: SK = 1 :2: 1 and 10g NPK/polibag), M4D2 (CP : AS : SK = 1: 1: 2 n 5 g NPK/polibag), M1D3 (CP:AS : SK= 1:1:1 and 14 g NPK/polibag), M2D3(CP :AS: SK=2: 1:1 and 14 g NPK/polibag), M3D3 (CP: AS: SK 1: 2: 1 and 14gNPK/polibag),M4D3(CP: AS: SK 1: 1: 2 and 14 g NPK/polibag). Result of research that : (1) The composition of plant media was significant to the amount of leaf and root (2) The dose of NPK fertilizer was very significant to the height of plant.(3) Interaktion of plant media komposition with the dose of NPK fertilizer not significant for all of parameters.(4) The best of plant growth of the composition of plant media 1 : 2 :1 (M3) with the dose of NPK fertilizer 10 g/polibag.